Does Demographic Pattern Matter for Sustainable Infrastructure Policy?. (2015) - Hermawan, Ferry; Rachmawati, Tutik; Wahyono, Herry Ludiro
Abstract: Crafting public policy that matches with the growing population requires a strategic approach to harmonise with sustainable infrastructure development. Indonesia with more than a quarter billion populations has a distinctive character in the archipelago area. Considering the fact that government capacity is low in the good infrastructure provision, hence it will create competitiveness among private sectors involved in the provision of public infrastructure, which further will path the way to a much more accepted infrastructure development and meet the need of the growing population. Sustainable infrastructure development requires the establishment of good quality life, although it would be challenging for policy maker in the dynamic pattern of demography. The research aims is to investigate whether the demographic pattern matter for sustainable infrastructure policy. It is important to study as to whether infrastructure policies have been designed with the consideration of population pattern. Further, it is important also to study the Indonesian development planning experience in regards to demographic pattern. This research presents a historical review of National Development Planning of Indonesia compared with population data simulation since 1960-2010. The data were collected from secondary resources and accompanied by document analysis. The results confirmed that macroeconomic, ecological and individual welfare rationales are predominant in the policy making.